Transverse vibrations driven negative thermal expansion in a metallic compound Gd Pd3 B0.25 C0.75 - Pandey A.; Mazumdar C.; Ranganathan R.; Tripathi S.; Pandey D.; Dattagupta S. (My University, 2025)
We have observed negative thermal expansion (NTE) in a metallic, polycrystalline, and structurally ordered cubic compound Gd Pd3 B0.25 C0.75. Our analysis suggest that the NTE observed in this compound does not stems from valence or magnetic instability of lattice ions, which is in general the case of metallic compounds exhibiting such an anomaly. We propose a possible alternative mechanism, namely, the transverse vibrations at low temperatures arising from site anisotropy, that induce the lattice contraction thereby resulting in isotropic NTE. The observed NTE also reflects its effect on the electrical transport properties of this compounds. © 2008 American Institute of Physics.